Design Thinking's Role in Enhancing User Experience on Fashion Campus with Attractive UI/UX Design - Rasmila Rasmila; M. Hafizin Syahid Walillah (LPPM Universitas Islam 45 Bekasi, 2023)
Since the Covid pandemic, it has become popular to purchase used clothing. However, there are still obstacles to purchasing used apparel, such as limited selection, quality, and lack of product information. To address this issue, Fashion Campus, a platform for purchasing and selling used clothing with an attractive UI and excellent UX, was developed. UI/UX design is essential for ensuring a positive user experience, and Figma, a web-based vector design application, is being utilized for collaborative efforts. The Design Thinking method is used to increase the efficiency of collaboration and reduce development time. This iterative process permits researchers to gain a deeper understanding of users, to challenge presumptions, and to redefine existing problems in order to identify strategies and solutions. By focusing on the user experience, Design Thinking can lead to the creation of UI/UX Fashion Design by identifying new methods to enhance that experience.